An Electric‐Field‐Responsive Discotic Liquid‐Crystalline Hexa‐peri‐Hexabenzocoronene/Oligothiophene Hybrid. (19th December 2013) - Hu, Nan; Shao, Renfan; Shen, Yongqiang; Chen, Dong; Clark, Noel A.; Walba, David M.
<x xml:space="preserve">Abstract</x> A novel hexa‐peri‐hexabenzocoronene/oligothiophene hybrid is shown to self‐assemble into a hexagonal columnar liquid crystalline phase, and respond to applied electric fields resulting in uniform homeotropic or parallel alignment depending upon the electrode structure. Furthermore, the columnar orientation can be maintained even after removal of the electric field unless the material is heated above the clearing temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>